Pengaruh kualitas produk, diskon harga, dan promosi terhadap keputusan pembelian - M. Puspitasari, Devy; Herdian, Risma (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This study aims to determine the effect of product quality, discounts, and promotions on purchasing decisions: an empirical study on Griya Department Stores. The method used in this study is multiple regression analysis. The data used is primary data collected through collecting questionnaires from 100 Griya Department Store customers. Empirical investigations show that product quality and promotional power have a strong influence on purchasing decisions. While the price discount has no relationship with the purchase decision, Good product quality accompanied by proven promotional power strengthens the customer's decision to buy. High price discounts do not always affect the customer's decision to buy the product. This research is useful for encouraging department store management to pay attention to their promotions so that they are right on target and reach their market. Excellent product quality, management must pay attention to give customers confidence that they are purchasing from the right place.